'A Distant Idea of Proximity': How Keats Handled Beauty. (2nd January 2017) - Allen, Michael Patrick
Abstract: This essay brings together two questions that worried John Keats: first, can beautiful things (urns, mythologies, poems) suffer damage through mishandling or misinterpretation? Second, must the poet pursue his vocation in solitude? In his letters, Keats's thoughts on solitude and sociability continually intersect with his fears of damage to the beautiful. His preoccupation with thinking as touching, and touching as injury, led him to contemplate leaving the city for a hermetic solitude in which his poems would be 'not fingerable over by men.' On the other hand, Keats worried about being out of touch with those closest to him. He cherished the 'silent moulding and influencing power' of amicable proximity. Keats offered his correspondents what he calls 'a distant idea of proximity.' I show how this 'interassimilation' of his 'solitary reperception of beauty' and textual sociability are legible in his manuscripts.